An agent-based framework for production software defined networks. (2016) - Izard, Ryan; Deng, Juan; Wang, Qing; Xu, Ke; Wang, Kuang-Ching
Software defined networking (SDN) is lauded to be the paradigm of choice for the next generation networks. While academia explores use cases in various contexts, industry has focused on data centre networks' limited but intense needs. There is a significant range of complex and application-specific network services that can potentially benefit from SDN, but introduction and adoption of such solutions remains slow in production networks. One impeding factor is the lack of a simple yet expressive enough framework applicable to all SDN services across production network domains. Without a uniform framework, SDN developers create disjoint solutions, resulting in untenable management and maintenance overhead. In this paper, we propose an agent-based framework, which enabled the development of three distinct SDN services addressing the needs of network operators, application providers, and application users. The architecture facilitates application-oriented SDN design with an abstraction composed of software agents on top of the underlying network.